Everything lies in a space: cultural data and spatial reality. (19th March 2021) - Seaver, Nick
Abstract: This essay examines the use of spatializing techniques for analysing cultural data, drawing on fieldwork with developers of music recommender systems in the United States. Comparing these practices with related analytic techniques developed by post‐war cognitive anthropologists, it explores three broad topics: how such techniques engender a sense of continuous, enveloping milieu from discrete and often sparse data; how spatialization is used to grant culture a kind of reality rooted in pragmatic action and scientific quantification; and how spatial representations of culture are essentially anticipatory for the people who make them, transforming the near future into the nearby. Abstrait: Tout n'est qu'espace : données culturelles et réalité spatiale Résumé En s'appuyant sur un travail de terrain réalisé aux États‐Unis auprès de développeurs de systèmes de recommandation musicale, cet article s'intéresse à l'utilisation de techniques de spatialisation dans l'analyse de données culturelles. En comparant ces pratiques avec des techniques analytiques similaires développées par l'anthropologie cognitive d'après‐guerre, l'auteur explore trois grandes questions : comment ces techniques créent l'impression d'un milieu continu et enveloppant à partir de données distinctes et souvent rares ; comment la spatialisation est employée afin de conférer à la culture une sorte de réalité enracinée dans l'action pragmatique et la quantification scientifique ; et comment les représentations spatiales de la culture s'avèrent fondamentalement anticipatives pour les personnes qui les construisent, permettant une géolocalisation de l'avenir proche.